Optimizing the Electrochemiluminescence of Readily Accessible Pyrido[1, 2‐α]pyrimidines through "Green" Substituent Regulation. Issue 3 (4th February 2021) - Zhang, Ruizhong; Cheng, Jun; Yang, Liuqing; Wong, Jonathan M.; Ralph Adsetts, Jonathan; Wang, Ruiyao; Liu, Jiyan; Ding, Zhifeng; Wang, Hong‐Bo
Abstract: Bright and low‐cost emitting organic molecules are very desirable for electrochemiluminescence (ECL). Here, we report a facile one‐step, three‐component reaction of readily available precursors to synthesize pyrido[1, 2‐α]pyrimidine derivatives (1 –4 ), all which give off green photoluminescence (PL). In contrast, the electrochemistry and ECL properties of these luminophores are affected by the extent of the conjugation and the nature of the peripheral substituents. Density functional theory (DFT) calculations identified the aromatic chain substitution could extend the conjugation of pyrido[1, 2‐α]pyrimidine core and stabilize the electrogenerated radicals required for generation of an excited state, affording pyrido[1, 2‐α]pyrimidine 3 the highest ECL activity among the studied samples. ECL in annihilation route confirmed weak emission, but great improvement was made using oxidizing co‐reactant species (benzoate radical from benzoyl peroxide, BPO) with an efficiency of 43 % relative to that of Ru(bpy)3 (PF6 )2 . The pyrido[1, 2‐α]pyrimidine 3/ BPO system is more robust than those of reducing co‐reactant species [tri‐ n ‐propylamine radical or 2‐(dibutylamino) ethanol radical] and is one of the highest among the reported organic electrochemiluminophores. ECL spectroscopy revealed that the monomeric excited states were the main species to emit light. Their straightforward, one‐step, green synthesis, and their structure tunability represent significant advantages in the development of readily accessible dyes for PL and especially ECL applications. Abstract : The green light : A one‐step, three‐component reaction is explored for the synthesis of pyrido[1, 2‐α]pyrimidine derivatives from readily available precursors and green solvent. All synthesized pyrido[1, 2‐α]pyrimidines give off green photoluminescence (PL) and electrochemiluminescence (ECL). Different from their structure‐independent PL, the aromatic chain substitution could extend the conjugation of pyrido[1, 2‐α]pyrimidine core and stabilize the electrogenerated radicals required for the generation of an excited state, affording pyrido[1, 2‐α]pyrimidine 3 the highest ECL activity (as high as 43 % relative to Ru(bpy)3 (PF6 )2 standard).